2009
DOI: 10.1021/ic900022s
|View full text |Cite
|
Sign up to set email alerts
|

Redox Isomerism in the Lanthanide Complex [(dpp-Bian)Yb(DME)(μ-Br)]2 (dpp-Bian = 1,2-Bis[(2,6-diisopropylphenyl)imino]acenaphthene)

Abstract: Ytterbium reacts with 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene (1, dpp-Bian) in 1,2-dimethoxyethane (DME) to give complex (dpp-Bian)Yb(DME)(2) (2). Oxidation of 2 with an 0.5 mol equivalent of dibromostilbene affords dimeric compound [(dpp-Bian)Yb(DME)(mu-Br)](2) (3). Molecular structures of 2 and 3 were determined by single-crystal X-ray analysis. In complex 3 in a DME solution, a temperature-dependent reversible intramolecular electron transfer between the ligand and the metal takes place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 37 publications
2
62
0
Order By: Relevance
“…while the Yb−Br bond lengths of 4·3thf (2.8932(2) and 2.9216(3) Å) are comparable in length to those of the six-coordinate ytterbium complex [Yb(dpp-Bian)(μ-Br)(dme)] 2 (dpp-Bian = 1,2-bis{(2,6-diisopropylphenyl)imino}acenaphthene; 2.8673(9) and 2.9325(9) Å) 28. Once again, intermolecular C−H···C(π) interactions between neighboring phenyl rings are present in the structures (refer to the CIF files in the Supporting Information).Molecular Structure of [K(18-crown-6)(thf) 2 ][C 5 Ph 4 H].…”
mentioning
confidence: 90%
“…while the Yb−Br bond lengths of 4·3thf (2.8932(2) and 2.9216(3) Å) are comparable in length to those of the six-coordinate ytterbium complex [Yb(dpp-Bian)(μ-Br)(dme)] 2 (dpp-Bian = 1,2-bis{(2,6-diisopropylphenyl)imino}acenaphthene; 2.8673(9) and 2.9325(9) Å) 28. Once again, intermolecular C−H···C(π) interactions between neighboring phenyl rings are present in the structures (refer to the CIF files in the Supporting Information).Molecular Structure of [K(18-crown-6)(thf) 2 ][C 5 Ph 4 H].…”
mentioning
confidence: 90%
“…Herein we report the synthesis and a combined X-ray crystallography plus SQUID study of the new complex [{(dpp-bian)Yb(m-Cl)(dme)} 2 ] (1; dpp-bian = 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene), which turns out to be the first rare-earth-metal complex that exhibits genuine thermally induced redox isomerism in the solid state. Similar to its bromine analogue, [{(dpp-bian)Yb(m-Br)(dme)} 2 ], [6] complex 1 reveals intramolecular electron transfer between the metal and the dpp-bian ligand in solution as well; these data will be published elsewhere.Dimeric [{(dpp-bian)Yb(m-Cl)(dme)} 2 ] (1) can be prepared in two different ways: 1) reacting an excess of ytterbium (powder or pieces) with dpp-bian and YbCl 3 in 1,2-dimethoxyethane (dme) at reflux; or 2) by oxidation of [(dpp-bian)Yb(dme) 2 ][6] in dme solution with chlorine-containing substances, [7] for example, 1,2-dichloroethane. A wellresolved 1 H NMR spectrum of complex 1 can be obtained at low temperature.…”
mentioning
confidence: 97%
“…Dimeric [{(dpp-bian)Yb(m-Cl)(dme)} 2 ] (1) can be prepared in two different ways: 1) reacting an excess of ytterbium (powder or pieces) with dpp-bian and YbCl 3 in 1,2-dimethoxyethane (dme) at reflux; or 2) by oxidation of [(dpp-bian)Yb(dme) 2 ] [6] in dme solution with chlorine-containing substances, [7] for example, 1,2-dichloroethane. A wellresolved 1 H NMR spectrum of complex 1 can be obtained at low temperature.…”
mentioning
confidence: 99%
“…While redox-active ligands have been proven to impart interesting magnetic [8,9] or electrochemical [10][11][12] properties to the rare earth elements due to their ability to stabilize ligand radicals, [13,14] fewer examples exist that demonstrate productive electron movement for new bond formation. Mazzanti et al reported tetradentate Schiff base complexes of Nd, Eu, Tb,Ybthat, upon reduction, store two electrons in anew CÀC s bond.…”
mentioning
confidence: 99%